Broad spectrum antimicrobial activities from spore-forming bacteria isolated from the Vietnam Sea - Chau,Khanh Minh; Van Quyen,Dong; Fraser,Joshua M.; Smith,Andrew T.; Van,Thi Thu Hao; Moore,Robert J. (PeerJ, 2020)
The widespread occurrence of pathogenic bacteria resistant to last-line antibiotics has resulted in significant challenges in human and veterinary medicine. There is an urgent need for new antimicrobial agents that can be used to control these life threating pathogens. We report the identification of antimicrobial activities, against a broad range of bacterial pathogens, from a collection of marine-derived spore-forming bacteria. Although marine environments have been previously investigated as sources of novel antibiotics, studies on such environments are still limited and there remain opportunities for further discoveries and this study has used resources derived from an under-exploited region, the Vietnam Sea. Antimicrobial activity was assessed against a panel of Gram-positive and Gram-negative bacteria, including several multi-drug resistant pathogens. From a total of 489 isolates, 16.4% had antimicrobial activity. Of 23 shortlisted isolates with the greatest antimicrobial activity, 22 were Bacillus spp. isolates and one was a Paenibacillus polymyxa isolate. Most of the antimicrobial compounds were sensitive to proteases, indicating that they were proteins rather than secondary metabolites. The study demonstrated that marine bacteria derived from the Vietnam Sea represent a rich resource, producing antimicrobial compounds with activity against a broad range of clinically relevant bacterial pathogens, including important antibiotic resistant pathogens. Several isolates were identified that have particularly broad range activities and produce antimicrobial compounds that may have value for future drug development.
Keywords: Antimicrobial; Bacteriocin; Bacillus; Paenibacillus; Broad-spectrum; Marine bacteria; Vietnam sea